Convergence of Multiple MAP3Ks on MKK3 Identifies a Set of Novel Stress MAPK Modules - Colcombet, Jean; Sözen, Cécile; Hirt, Heribert (Frontiers in Plant Science, 2016)
Since its first description in 1995 and functional characterization 12 years later, plant MKK3-type MAP2Ks have emerged as important integrators in plant signaling. Although they have received less attention than the canonical stress-activated MAPKs, several recent publications shed light on their important roles in plant adaptation to environmental conditions. Nevertheless, the MKK3-related literature is complicated. This review summarizes the current knowledge and discrepancies on MKK3 MAPK modules in plants and highlights the singular role of MKK3 in green plants. In the light of the latest data, we hypothesize a general model that all clade-III MAP3Ks converge on MKK3 and C-group MAPKs, thereby defining a set of novel MAPK modules which are activated by stresses and internal signals through the transcriptional regulation of MAP3K genes.